BusAI: An BDI-agent-based Urban Transport Information System - Lira, Lucas; Serafim, Andrei; Lazarin, Nilson; Freitas, Bruno; Pantoja, Carlos (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC); 2025: Anais do XIX Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações, 2025)
This paper proposes an information system for urban transport, leveraging an Embedded Multi-agent System based on the Belief-Desire-Intention (BDI) model. It involves developing a simulated environment where AI agents, implemented using Jason and communicating via Javino, manage real-time bus data and interact with virtual information points. This system aims to enhance the urban mobility experience by providing passengers with accurate, dynamic information regarding bus location, occupancy, and estimated arrival times, thereby improving operational efficiency and passenger satisfaction. This paper details a proof of concept demonstrating the viability of this multi-agent approach in addressing real-world public transport challenges.